Sister Maria Jose's nodule as a presentation of a strangulated umbilical hernia - González, Yazmin G.; Lopez, Rodolfo I.; Villarreal, Rodrigo; Hernandez, Reyger G.; Cruz, Alexis (International Journal of Research in Medical Sciences, 2024)
The “sister María José” umbilical nodule is a metastatic nodule associated with advanced digestive and gynecological tumors. Skin metastases due to gynecological tumors are not frequent, they only represent 1 to 3% of patients with intra-abdominal cancer and in most cases, they have a poor prognosis. One of the most common types of skin metastasis is the one that occurs at the umbilical level. A case of sister María José nodule is presented as a presentation of a strangulated umbilical hernia in a 67-year-old female patient with a history of ovarian cancer. Exploratory laparotomy was performed with the findings of: tumor in the abdominal wall measuring 10×7×6 cm. The histopathological result is carcinoma with a mucoproducing tubulopapillary pattern. With satisfactory post-surgical evolution and discharged home after 72 hours. Although the initial diagnosis in this patient was a strangulated umbilical hernia due to the clinical presentation and the ultrasound report, we were able to conclude that the definitive diagnosis was “sister María José nodule due to the result of the histopathological report and the history of ovarian cancer 6 years previous.